An integrative analytical model for the water-energy-food nexus: South Africa case study. Issue 109 (July 2020) - Nhamo, Luxon; Mabhaudhi, Tafadzwanashe; Mpandeli, Sylvester; Dickens, Chris; Nhemachena, Charles; Senzanje, Aidan; Naidoo, Dhesigen; Liphadzi, Stanley; Modi, Albert T.
Highlights: WEF nexus sustainability indicators are a means of assessing resource management in an integrated manner. The developed model eliminated "a silo" approach in resource development by assessing resource management as a single unit. The model has established numerical relationships among the WEF nexus, indicating priority areas for intervention. The model assessed the progress towards achieving related SDGs to achieve sustainability by 2030. Abstract: The missing link between cross-sectoral resource management and full-scale adoption of the water-energy-food (WEF) nexus has been the lack of analytical tools that provide evidence for policy and decision-making. This study defined WEF nexus sustainability indicators, from where an analytical model was developed to manage WEF resources in an integrated manner using the Analytic Hierarchy Process (AHP). The model established quantitative relationships among WEF sectors, simplifying the intricate interlinkages among resources, using South Africa as a case study. A spider graph was used to illustrate sector performance as related to others, whose management is viewed either as sustainable or unsustainable. The model was then applied to assess progress towards the Sustainable Development Goals in South Africa. The estimated integrated indices of 0.155 and 0.203 for 2015 and 2018, respectively, classify South Africa's management of resources as marginally sustainable. The model is a decision support tool that highlights priority areas for intervention.